1983
DOI: 10.1055/s-2007-1018648
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Peptide Effects on Insulin Release and c-AMP in Islets of Langerhans

Abstract: The time course and specificity of the effect of opioid peptides on c-AMP production in the islets of Langerhans was examined. An enkephalin analogue, d-Ala2Me Phe4 Met(O)-ol enkephalin (DAMME, Sandoz) produced a significant stimulation of basal c-AMP levels, with a peak of stimulation at 5 minutes and a decline thereafter. These changes in intracellular c-AMP levels were of the same order of magnitude as those induced by other secretagogues, but did not coincide in time with the more rapid peak of enkephalin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 15 publications
0
23
1
Order By: Relevance
“…Therefore, the radioreceptor-active dynorphin (Table 2) and radioimmunoassayable /-endorphin ( (Ipp et al, 1978;Ryder et al, 1980;Curry et al, 1987) and of K-opiate agonists (Green et al, 1983b;Toyota et al, 1985) to stimulate insulin release, at physiological concentrations between I and 10 nm, from rat islets of Langerhans. Similarly, several reports exist showing direct effects of opiate agonists on liver function of the rat in vitro (Allan et al, 1983;Matsumura et al, 1984 (Ipp et al, 1978;Green et al, 1980;Kanter et al, 1980).…”
Section: Radioimmunoassaymentioning
confidence: 99%
“…Therefore, the radioreceptor-active dynorphin (Table 2) and radioimmunoassayable /-endorphin ( (Ipp et al, 1978;Ryder et al, 1980;Curry et al, 1987) and of K-opiate agonists (Green et al, 1983b;Toyota et al, 1985) to stimulate insulin release, at physiological concentrations between I and 10 nm, from rat islets of Langerhans. Similarly, several reports exist showing direct effects of opiate agonists on liver function of the rat in vitro (Allan et al, 1983;Matsumura et al, 1984 (Ipp et al, 1978;Green et al, 1980;Kanter et al, 1980).…”
Section: Radioimmunoassaymentioning
confidence: 99%
“…The discrepancies between the results of Dr. Green and his coworkers and ours may be ascribed to the methodological differences, i.e., in our study the perfusion technique of the isolated pancreas was used, whereas in his study the incubation of the isolated islets was done. We used dynorphin (1-17) whereas he used dynorphin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The concentration of dynorphin was higher in our study than that in theirs.…”
Section: Discussionmentioning
confidence: 51%
“…Recently Green et al (1980Green et al ( , 1983 reported that dynorphin stimulated insulin secretion via an increase in both cyclic AMP and calcium influx in the islets. On the contrary, rimorphin and dynorphin as well as morphine (3.95 X 10-8 M) inhibited glucose-induced insulin secretion in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green et al 24 first showed that morphine and met-enkephalin were able to stimulate glucose-induced insulin release in isolated pancreatic isles, an effect that was observed to develop rapidly, representing the first phase of pancreatic insulin release and which could be blocked by naloxone pre-treatment and therefore, showing an opioid-receptor mediated effect. A number of studies that followed confirmed the results of Green et al either directly [26][27][28] 24, 26, 27; 28, 29, 32, 33 , while others have shown the opposite inhibitory effect [34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 75%